Teachers’ Competence in Managing Learners’ Performance Tasks - M. Talaboc, Melna; A. Buquia, William (Polaris Global Journal of Scholarly Research and Trends, 2024)
Teachers’ competence plays a crucial role in learners’ performance tasks across various educational settings. In this context, this paper aimed to determine the level of teachers’ competence in learners’ performance tasks of the public elementary schools in an island district in a large-sized division in central Philippines during the school year 2022-2023. Data for this descriptive study was collected from 104 respondents using a self-made survey questionnaire that has passed the rigorous tests of validity and reliability. The ensuing analysis showed a high level of teachers’ competence in learners’ performance tasks during the school year 2022-2023. Further analysis showed a significant relationship between teachers’ competence in learners’ performance tasks. The same data showed a high level of teachers’ competence in learners’ performance tasks. This aims to unveil valuable insights and draw meaningful conclusions that contribute to the overall objectives of the research study, particularly in mentoring and designing lessons in their discipline that use the 21st pedagogy, assessment style, and technology. Regarding teachers’ competence in learners’ performance tasks, the areas of the learning process, integration to real-life situations, and diverse learners were rated with very high-level equivalents. However, the area of knowledge and skill was rated as high level.